Removal of Methylene Blue Dye from Aqueous Solution by Adsorption on Leonardite Char - Hemaviboon, Khaunjit; Klamtet, Jintana (Naresuan University Journal: Science and Technology (NUJST), 2020)
The present investigation was studied the adsorption of MB dye from aqueous solution by using leonardite carbonized as adsorbent at various temperatures in a batch experiment. The prepared leonardite adsorbents were characterized by FTIR, BET, SEM and XRD.  The BET results showed that LN700 gave highest micropores in the surface which is in agreement with adsorption efficiency study. The optimum parameters for MB adsorption onto LN700 such as pH of MB solution, contact time and adsorbent particle size were investigated. The optimum contact time for MB removal onto 45-75 µm LN700 was 30 min.at pH value of 10. The adsorption kinetic of MB onto LN700 shows linear plot of pseudo second-order model and the adsorption at equilibrium data fitted well to Langmuir isotherm model which the maximum adsorption capacity was 26.32 mg MB g - 1 .   Keywords : Leonardite, Adsorption, Methylene blue